Delayed fracture healing - Mick, Paul; Fischer, Christian (Seminars in musculoskeletal radiology, 2022)
Physiologic bone healing involves numerous parameters, such as microstability, fracture morphology, or tissue perfusion, to name just a few. Slight imbalances or a severe impairment of even one of these factors may, as the figurative weakest link in the chain, crucially or completely inhibit the regenerative potential of a fractured bone. This review revisits the physiology and pathophysiology of fracture healing and provides an insight into predispositions, subtypes, diagnostic tools, and therapeutic principles involved with delayed fracture healing and nonunions. Depending on the patients individual risk factors, nonunions may develop in a variety of subtypes, each of which may require a slightly or fundamentally different therapeutical approach. After a detailed analysis of these individual factors, additional diagnostic tools, such as magnetic resonance imaging (MRI), dynamic contrast-enhanced MRI, sonography, or contrast-enhanced ultrasonography, may be indicated to narrow down the most likely cause for the development of the nonunion and therefore help find and optimize the ideal treatment strategy.
Gesehen am 16.06.2023